Organizational Commitment and Culture on Teachers’ Organizational Citizenship Behavior in Elementary School - Muhammad Yusril Amin; Rima Rahmayanti (Al-Qalam Institue, 2026)
This study aims to examine the influence of organizational commitment and organizational culture on teachers’ Organizational Citizenship Behavior (OCB), both partially and simultaneously. A quantitative approach with a descriptive and causal-associative research design was employed. The study involved 41 teachers selected through a saturated sampling technique. Data were collected using a structured questionnaire based on a four-point Likert scale and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, partial (t) tests, simultaneous (F) tests, and the coefficient of determination. The results indicate that organizational commitment has a positive and significant effect on teachers’ OCB (t = 2.898, p = 0.006), while organizational culture also has a positive and significant effect with a stronger influence (t = 6.421, p < 0.001). Simultaneously, organizational commitment and organizational culture significantly influence teachers’ OCB (F = 61.169, p < 0.001), explaining 75.1% of the variance in OCB (Adjusted R² = 0.751). These findings imply that strengthening teachers’ organizational commitment and fostering a supportive organizational culture are essential strategies for promoting voluntary, collaborative, and extra-role behaviors that enhance organizational effectiveness and improve the quality of educational management